2017
DOI: 10.1016/j.spinee.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

What questionnaires to use when measuring quality of life in sacral tumor patients: the updated sacral tumor survey

Abstract: Background context Patient reported outcomes are becoming increasingly important when investigating results of patient and disease management. In sacral tumor patients symptoms can vary substantially, therefore no single questionnaire can adequately account for the full spectrum of symptoms and disability. Purpose The purpose of this study is to analyze redundancy within the current sacral tumor survey and make a recommendation for an updated version based on the results and patient and expert opinions. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…As survival improves for orthopedic oncology patients, increased interest has developed in patient-reported outcomes (PROs), particularly for function and HRQoL. [28][29][30] The SF-36 is a generic measure of HRQoL and is widely used in healthcare to evaluate patient's self-perceived health. 31,32 Interpreting outcome measures presents a challenge, as statistical significance does not always translate into clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…As survival improves for orthopedic oncology patients, increased interest has developed in patient-reported outcomes (PROs), particularly for function and HRQoL. [28][29][30] The SF-36 is a generic measure of HRQoL and is widely used in healthcare to evaluate patient's self-perceived health. 31,32 Interpreting outcome measures presents a challenge, as statistical significance does not always translate into clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from Colman et al (73), concluded that PROMIS was a superior and more responsive tool compared to EQ-5D, NDI, and ODI for assessing quality of life for 27 patients who underwent surgery and eight patients who underwent RT for spine tumors. Another study by van Wulfften Palthe et al (74) compared PROMIS to number of older PRO measuring systems for patients with sacral spinal tumors, with the researchers recommending that PROMIS surveys be used to assess quality of life in areas such mental health, physical health, pain, gastrointestinal symptoms, sexual function, and social health. Given the comprehensiveness, efficiency, adaptability, and validity of PROMIS, the literature appears to be trending towards this becoming the gold standard for assessing PRO for metastatic spine disease.…”
Section: Promismentioning
confidence: 99%
“…Lastly, patient reported outcomes were not collected for most patients in this study. While patient reported outcomes for chordomas and other primary spine tumors are still being defined, van Wulfften et al recently published a revised sacral tumor survey that may be appropriate to use in patients with sacral chordomas going forward (28).…”
Section: Study Limitationsmentioning
confidence: 99%